2019
DOI: 10.1002/ygh2.339
|View full text |Cite
|
Sign up to set email alerts
|

External validation of an algorithm combining multi‐analyte blood tests (FibroTest‐LCR1‐LCR2) to identify subjects at risk of hepatocellular carcinoma in patients with chronic liver disease

Abstract: Summary Background and Aims The early non‐invasive prediction of hepatocellular carcinoma in patients with chronic liver disease, without or with cirrhosis, is needed. The algorithm FT‐LCR1‐LCR2 which sequentially combines the FibroTest and two multi‐analyte‐tests (LCR1‐LCR2) and increased the performance of alfa‐foeto‐protein (AFP) alone, was constructed and internally validated in the prospective FibroFrance cohort. The first aim was to externally validate the sensitivity and the 5‐year prognostic value of F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 10 publications
2
6
0
Order By: Relevance
“…LCR1-LCR2 has also been externally validated in a case control study of 149 prospectively enrolled patients in the Bondy Cohort. 12 The aim of the present study was to externally validate LCR1-LCR2 with the previously identified cutoffs of the Original-Study, in a sustainability analysis of patients with chronic hepatitis C, prospectively included in the large Hepather cohort, whatever the stage of fibrosis at inclusion. 7…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…LCR1-LCR2 has also been externally validated in a case control study of 149 prospectively enrolled patients in the Bondy Cohort. 12 The aim of the present study was to externally validate LCR1-LCR2 with the previously identified cutoffs of the Original-Study, in a sustainability analysis of patients with chronic hepatitis C, prospectively included in the large Hepather cohort, whatever the stage of fibrosis at inclusion. 7…”
Section: Discussionmentioning
confidence: 99%
“…22 Our ambispective (both prospective and retrospective) analysis was useful to assess health outcomes with a long induction period and exposures. 12…”
Section: Sample Size and Large Stage Spectrummentioning
confidence: 99%
See 1 more Smart Citation
“…The HECAM-FibroFrance Group previously reported and externally validated the LCR1 and LCR2 tests to identify individuals at high risk of HCC in a cohort of patients with any cause of chronic liver disease (7,8) potentially curable, all were smaller than 30 mm.…”
mentioning
confidence: 99%
“…The HECAM-FibroFrance Group previously reported and externally validated the LCR1 and LCR2 tests to identify individuals at high risk of HCC in a cohort of patients with any cause of chronic liver disease. 7 , 8 LCR1-LCR2 is a multi-analyte blood test combining proteins involved in liver cell repair (apolipoprotein-A1, haptoglobin), known HCC risk factors (gender, age, gamma-glutamyltransferase), a marker of fibrosis (alpha2-macroglobulin) and alfa-fetoprotein, a specific marker of HCC. In this issue of JHEP Reports , the HECAM consortium and the ANRS CO22 Hepather cohort present an external validation of LCR1-LCR2 in patients with chronic hepatitis C from the ANRS CO22 Hepather cohort.…”
mentioning
confidence: 99%